Pengelolaan Kurikulum Merdeka di SMK Negeri 2 Padang - Pramudia Yordi Hermawan; Jasria Jasria (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2023)
Abstract The purpose of this study was to gather information about the management of the independent curriculum (kurikulum merdeka) at SMK Negeri 2 Padang in terms of the aspects of lesson planning, implementation of learning, learning assessment and learning follow-up. This type of research is descriptive. The instrument in this research is a questionnaire. The results of the study stated that the independent curriculum (kurikulum merdeka) management at SMK Negeri 2 Padang in aspects 1) learning planning with an average score of 4.12 was in the good category, 2) learning implementation with an average score of 4.09 was in the good category, 3) learning assessment with an average score of 4.07 was in the good category, 4) follow-up learning with an average score of 3.88 was in the good category. It can be concluded that the kurikulum merdeka management at SMK Negeri 2 Padang is in the good category with an average score of 4.04.